Qualified nurses – nurse prescribing – qualitative research - Corfield, Laura (2010)
Abstract Aim: The aim of this study was to explore the impact of a non-medical prescribing course on the personal lives of its participants. Background: Within the literature on non-medical prescribing education, little attention has been given to the personal impact such a course has on its students. Current literature concerning non-medical prescribing education has mainly focussed on the professional issues of prescribing, with little focus on the stressors experienced by students and the causes of such stress. Method: Quantitative and qualitative methods were used for data collection, with one interview followed by questionnaires distributed to a cohort of non-medical prescribing students at the point of course assessment. Results: Themes identified from the interview and questionnaires were ‘support from managers’, ‘domestic issues’ and ‘individual stress levels’. It was found that nearly one third of participants felt that they had received insufficient support from their managers during the course, over a third of the sample stated that they applied for extenuating circumstances for domestic reasons, and all participants reported some level of stress during the course, with the majority reporting moderate to severe stress/anxiety during the course. Time management was also reported as a significant issue.